Practique motives in padel players regarding age, level and gender - Sánchez-Alcaraz Martínez, B. J.; Muñoz Marín, D.; Courel Ibáñez, J.; Grijota Pérez, F. J.; Chaparro Herrera, R.; Díaz García, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of this study was to determine the motivations that may explain the actual increment in padel practice through different socio-demographic parameters such as sex, age or category. A total of 77 participants (43male and 34female), completed a questionnaire addressing sociodemographic information and the "Measurement Scale Motives for Physical Activity-Revised (MPAM-R)". The results point outed enjoyment (6.07) as the most valued reason for practice. Other appreciated reasons were competition (5.43), fitness / health (5.49) and sociability (5.07), being appearance the least scored (3.97). Significant differences were observed between categories (p<0.05). Current data provide useful information to sports centres managers in designing action plans to improve the quality of services offered, as well as supporting the teaching and learning process in padel.